Penguatan Potensi Wakaf Sebagai Sarana Pemberdayaan Ekonomi Masyarakat di Kalurahan Jetis Kapanewon Saptosari Kabupaten Gunung Kidul Daerah Istimewa Yogyakarta - Fakultas Hukum Universitas Negeri Surabaya; Farida Prima Pratista; Nurul Hikmah; Hikam Hulwanullah; Nailul Ulah Al Chumairoh Machfud (Fakultas Hukum, Universitas Negeri Surabaya, 2025)
Waqf is an Islamic philanthropic activity that has a strategic function in various instruments. Gunungkidul regency, located in the Special Region of Yogyakarta, is one of the regions that has received an award as a waqf city in Indonesia, but the potential does not necessarily mean that all communities can optimally utilize waqf assets. The purpose of community service activities in Jetis village is to provide education and better understanding to the community regarding the provisions, concepts, and potential of waqf, as well as the implementation of Islamic values in social and economic activities. The method used is educational in the form of socialization using a participatory approach. From this study, it was found that public awareness of the importance of productive waqf asset management as economic added value is quite good, but there is still a lack of understanding about the sustainable utilization of waqf assets. Through the dissemination of information on strengthening the potential of waqf, it is hoped that the community will be able to improve their understanding of the regulations governing waqf management in Indonesia, and that the community will be able to actively participate in the utilization of waqf assets, until achieving economic independence.